2020
DOI: 10.1590/s1980-220x2019013703634
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da entrevista motivacional no autocuidado de pessoas com insuficiência cardíaca: ensaio clínico randomizado

Abstract: RESUMO Objetivo: Analisar o efeito da entrevista motivacional no autocuidado de pessoas com insuficiência cardíaca crônica. Método: Ensaio clínico randomizado, multicêntrico, dividindo as pessoas em grupo intervenção (n=59) e grupo controle (n=59), acompanhadas por 60 dias nos centros do Brasil e Uruguai. O grupo intervenção recebeu três consultas por entrevista motivacional, com intervalo de 30 dias, e o grupo controle manteve o acompanhamento convencional nas clínicas especializadas. Os dados foram avaliad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 21 publications
1
13
0
2
Order By: Relevance
“…17,20,21,23,24 Several studies, including ours, confirmed that the same healthcare professionals implemented the MI program and the conventional educational programs 19,20,22,25 ; this information was not reported, however, in a number of other studies. 17,21,23,24 In terms of duration, our intervention took place for a longer period than in other studies, whose interventions lasted less than 1 month 21,22 or between 1 and 3 months. 17,19,20,[23][24][25] Several studies did not report interview duration, 17,[19][20][21] which in our case was 45 minutes (baseline visit) or 30 minutes (other visits).…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…17,20,21,23,24 Several studies, including ours, confirmed that the same healthcare professionals implemented the MI program and the conventional educational programs 19,20,22,25 ; this information was not reported, however, in a number of other studies. 17,21,23,24 In terms of duration, our intervention took place for a longer period than in other studies, whose interventions lasted less than 1 month 21,22 or between 1 and 3 months. 17,19,20,[23][24][25] Several studies did not report interview duration, 17,[19][20][21] which in our case was 45 minutes (baseline visit) or 30 minutes (other visits).…”
Section: Discussionmentioning
confidence: 68%
“…17,19,20,[23][24][25] Several studies did not report interview duration, 17,[19][20][21] which in our case was 45 minutes (baseline visit) or 30 minutes (other visits). Regarding the delivery format, several studies, including ours, held face-to-face sessions, 21,23,24 whereas others combined face-to-face and telephone sessions. 17,19,20,22,25 The essential element in ensuring intervention reliability is monitoring, which in our case, was carried out in situ by a psychologist, an expert in MI, who coded nursing interventions using the MITI 38 during visits with patients.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations